Siberian High as an important factor for development of cyclonic activity in the Far Eastern region in winter, spring and summer seasons - S. Yu. Glebova (Известия ТИНРО, 2021)
Influence of the Siberian High longitudinal position on cyclonic activity over the Far Eastern Seas and the Pacific Ocean in winter, spring and summer is considered. Eastward shift of this atmospheric center causes general decreasing of number of cyclones over the region, but their intensity increases; on the contrary: cyclones are more frequent but weaker when the Siberian High is located in western position. The Siberian High, being a winter center, cannot influence directly on spring and summer cyclones, but it influences on formation of the Far Eastern Low, which intensity correlates with number and intensity of spring and summer cyclones.